Wettability of AlSi7Mg alloy on alumina, spinel, mullite and rutile and its influence on the aluminum melt filtration efficiency. (15th July 2018) - Voigt, Claudia; Ditscherlein, Lisa; Werzner, Eric; Zienert, Tilo; Nowak, Rafal; Peuker, Urs; Sobczak, Natalia; Aneziris, Christos G.
Abstract: Despite the application of aluminum melt filtration with ceramic foam filters since the 1960s the process is not fully understood. Outstanding issues are for example the influence of the wetting behavior and filter chemistry on the filtration efficiencies. Contact angle measurements by the sessile drop method coupled with non-contact heating and capillary purification technique were conducted at 730 °C with AlSi7Mg alloy on the substrates of four different oxides (Al2 O3, MgAl2 O4, 3Al2 O3 ·2SiO2 and TiO2 ). The highest contact angle was measured on 3Al2 O3 ·2SiO2, followed by MgAl2 O4, Al2 O3 and TiO2 . Experimental values of contact angles were correlated with the evaluated filtration efficiencies of filtration trials performed at Constellium. They show a good correlation for inclusions smaller than 110 μm - the larger the contact angle the higher is the filtration efficiency. The adhesion forces of alumina inclusions on the four filter materials were experimentally estimated with an AFM in water based model system. The highest adhesion forces were measured on the Al2 O3 substrate, followed by the 3Al2 O3 ·2SiO2, the MgAl2 O4 and the TiO2 substrate. For inclusions >70 μm, both the measured filtration efficiencies for >70 μm and the adhesion forces increase by the following order of coatings: TiO2, 3Al2 O3 ·2SiO2, MgAl2 O4, Al2 O3 . Graphical abstract: Highlights: Contact angle measurements between the filter material and aluminum alloy at 730 °C were conducted. The measured contact angles were correlated with filtration efficiencies measured at Constellium. The contact angles and the filtration efficiencies show a good correlation for inclusions smaller than 110 μm. Adhesion forces of alumina inclusions on filter materials were measured an AFM in a water based model system. First experimental evidence of assumption that poorer wetting of aluminum and filter improvesthe filtration efficiency.